Pakej pembelajaran untuk kanak-kanak / Siti Azrina Abd Aziz - Siti Azrina, Abd Aziz (2002)
Pakej Pembelajaran untuk Kanak-kanak (PPK) is multimedia software, which is developed in CD-ROM form using Bahasa Melayu as the communication language The main users of this system are children aging between 3 to 6 years old. The learning materials for this software include the basic of reading, colouring, listening to the music and counting. PPK is developed using Macromedia Director 8.0, Paint, Sound Recorder, Paint Shop Pro and others. There are several main reasons why PPK is developed such as the evolving technology, less interest in children to learn, no time and guidance to teach the children, no suitable software, problems with existing learning tools and others. The methodology that has been chosen is Rapid Application Development (RAD) that uses prototyping concept. This is because it is difficult to get the information from the main users whom are the children. The information for developing this system is gathered from reading, researching and interviewing. The sources of the information are Internet, books, kindergarten teachers, parents and also from lecturers. There are a few teaching kindergarten children techniques that I have used in PPK such as Montessori method and "cahayaku" concept. Last but not least I hope this thesis can give benefit and invaluable information for everyone.